AP-1 oligodeoxynucleotides reduce aortic elastolysis in a murine model of marfan syndrome - Arif, Rawa; Zaradzki, Marcin; Remes, Anca; Seppelt, Philipp; Kunze, Reiner; Schröder, Hannes; Schwill, Simon; Karck, Matthias; Müller, Oliver J.; Hecker, Markus; Wagner, Andreas H.; Kallenbach, Klaus (Molecular therapy. Nucleic Acids, 2017)
Marfan syndrome is characterized by high expression of matrix metalloproteinases (MMPs) in aortic smooth muscle cells (AoSMCs) associated with medial elastolysis and aortic root aneurysm. We aimed to reduce aortic elastolysis through decrease of MMP expression with decoy oligodeoxynucleotides (dODNs) neutralizing the transcription factor activating factor-1 (AP-1). AP-1 abundance in nuclear extracts as well as MMP-2 and MMP-9 expression were significantly increased in isolated mAoSMC of mgR/mgR Marfan mice compared to wild-type cells. Exposure to AP-1 neutralizing dODNs resulted in a significant reduction of basal and interleukin-1β-stimulated MMP expression and activity in mAoSMCs. Moreover, increased migration and formation of superoxide radical anions was substantially decreased in mAoSMCs by AP-1 dODN treatment. Aortic grafts from donor Marfan mice were treated with AP-1- dODN ex vivo and implanted as infrarenal aortic interposition grafts in mgR/mgR mice. Pretreatment of aortic grafts with AP-1 dODN led to reduced elastolysis, macrophage infiltration, and MMP activity. Permeability of the endothelial monolayer was increased for dODN in mgR/mgR aortae with observed loss of tight junction proteins ZO-1 and occludin, enabling dODN to reach the tunica media. Targeting AP-1 activity offers a new potential strategy to treat the vascular phenotype associated with Marfan syndrome.